Botanical medicine in clinical practice - Preedy, Victor R.; Watson, Ronald R. [ (Ronald Ross)] (CABI, 2008)
Covers the safety and efficacy, of botanical treatments, and includes a chapter analysing the possible interactions of herbal remedies with prescription drugs. This book covers a range of plant products and their uses, divided into sections on topics such as treatments of cardiovascular diseases, and cancer